Management, Implementation and Effect of Village Fund Allocation on Regional Development During Covid-19 Pandemic - Demitria Olla, Vivi; Mareta, Sigit (KnE Social Sciences, 2023)
The allocation of Village Funds requires planning, monitoring, implementation, and accountability for its use. The implementation of village development must be in accordance with what has been planned in the planning process and the community. The Covid-19 pandemic has changed the order of various aspects of life, including Indonesia. The health, social, and economic sectors were most significantly affected. The economic sector is experiencing recession both at the global and national levels. Timor Island is one of the islands in Indonesia experiencing this. This problem cannot be separated in encouraging the national economic growth rate. This study aims to determine the impact of the Covid-19 pandemic on economic growth in Timor Island, especially Fatuneno Village. Economic growth in Timor Island became the center of attention, which had experienced a contraction to accelerate economic recovery in Indonesia. Utilizing Village Fund Allocation as community empowerment is the main source in developing and advancing village communities, from what is mandated by the central and regional governments prioritizing regional autonomy. The Village Fund allocation is fully utilized for community empowerment and welfare, marked by the development of agricultural land and several infrastructures to make it easier for the community to empower themselves and the environment. Small form so that the village is able to empower the community and village institutions to overcome poverty and reduce inequality, improve development planning and budgeting in the village, and improve village infrastructure development, in order to create a prosperous village. Keywords: management, village fund allocation, village welfare, village development, Covid 19 pandemic